The Role of Brand Equity in Mediating the Influence of Social Media Communication on Museum Revisit Intention in Jakarta - Widiyanto, Mohamad; Abdha, Muhammad Fadly Erzavi (GREENOMIKA, 2024)
This research was conducted with the aim of analyzing the influence of social media communication through brand equity on revisit intention at museums in Jakarta. A quantitative approach is used to answer the research problem formulation. The research sample was 220 museum visitors in Jakarta. The data analysis technique was carried out using partial least square analysis using the SmartPLs program. The research results show that social media communication has a significant effect on revisit intention and brand equity is able to mediate the influence of social media community on revisit intention at museums in Jakarta.